The Impact of Switching to a Second Antifibrotic in Patients With Idiopathic Pulmonary Fibrosis: A Retrospective Multicentre Study From the EMPIRE Registry - Gregor, Jakub; Adir, Yochai; Šterclová, Martina; Mogulkoc, Nesrin; Kramer, Mordechai R; Doubková, Martina; Plačková, Martina; Müller, Veronika; Studnicka, Michael; Žurková, Monika; Lacina, Ladislav; Lewandowska, Katarzyna; et al. (Archivos de bronconeumología, 2024)
INTRODUCTION: Most patients with idiopathic pulmonary fibrosis (IPF) treated with antifibrotics (AF) have progressive disease despite treatment. A switch of AF may improve survival, but evidence from randomised controlled trials is missing. We aimed to evaluate the efficacy of an AF switch on survival and FVC decline in patients from the European MultiPartner IPF registry (EMPIRE). METHODS: The study included 612 patients who discontinued the first antifibrotic therapy. Patients were grouped and analysed from two perspectives: (1) whether they had received a second antifibrotic treatment after the discontinuation of the first therapy, and (2) a reason for discontinuation of the first AF - "lack of efficacy" (LE) and "intolerance" (INT). RESULTS: While 263 (43%) of 612 patients received no second AF ("non-switched"), 349 (57%) patients switched. Overall survival was higher in patients who received a second AF (median 50 vs. 29 months; adjusted HR 0.64, P=0.023). Similarly, the annual FVC decline was significantly reduced in switched patients: -98ml/y in switched and -172ml/y in non-switched patients (P=0.023), respectively. The switched patients had similar risk for mortality in both LE and INT groups (adjusted HR 0.95, P=0.85). The high impact of switching on survival was demonstrated in LE patients (adjusted HR 0.27, P<0.001). CONCLUSION: The patients without a second AF had significantly shorter overall survival. Our analysis suggests the importance of switching patients with an ineffective first AF therapy to a second AF therapy.
Keywords: vitální kapacita; Registries; Treatment Outcome; registrace; retrospektivní studie; lidé; Idiopathic Pulmonary Fibrosis; pyridony; progrese nemoci; idiopatická plicní fibróza; Retrospective Studies; Disease Progression; Pyridones; výsledek terapie; Vital Capacity; Humans